ASPEK HUKUM PEMENUHAN RUANG TERBUKA HIJAU DAN PENERAPANNYA PADA PERUMAHAN DAN KAWASAN PERMUKIMAN DI KABUPATEN SIDOARJO - Nabilah Assa'diyah Tisya; Muh Ali Masnun (Universitas Negeri Surabaya, 2023)
The purpose of this research is to analyze the construction of Article 29 paragraph (2) of Law Number 26 of 2007 concerning Spatial Planning (UUPR) and the implementation of the handover of green open space in Sidoarjo Regency, moreover the implementation of Article 47 paragraph (4) of the Sidoarjo Regent Regulation Number 97 of 2021 concerning Procedures for The Delivery and Utilization of Housing Infrastructure, Facilities, and Utilities related to the handover, especially green open space has not been carried out optimally. This research uses a type of empirical research was used that used a qualitative approach with the use of primary and secondary data which was then collected through literature studies and interviews, then analyzed by descriptive-analysis methods. The results showed that article 29 paragraph (2) of the UUPR can be interpreted that the fulfillment of 20% of public green open space is the responsibility of the city / regency regional government, while private green open space is 10% fulfilled by the community both individually and in groups, private parties, and legal institutions / entities. Besides that why the submission delivery of infrastructure, facilities, and public utilities has not been carried out optimally, due to one of the obstacles that occurs is related to the lack of strict sanctions to enforce developers (developers), so they do not feel that they have an obligation to hand them over.